Catch-all Politics of Women Politicians in Organizing Political Parties in Banten Province - Mayrudin, Yeby Ma'asan; Utami, Wahyu Kartiko; Irawan, Peri; Afala, La Ode Machdani (Universitas Sultan Ageng Tirtayasa, 2025)
This article discusses the involvement of female politicians in organizing political parties that open up opportunities for the manifestation of catch-all politics in Banten. Catch-all politics is a strategy of political parties that embraces all parties, especially the women's community, to join and fight together. The research uses descriptive qualitative methods through data collection from informants, literature, and media studies to